2016
DOI: 10.1038/mp.2016.86
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of calcium channel antagonists in bipolar disorder and some considerations for their future development

Abstract: l-type calcium channel (LTCC) antagonists have been used in bipolar disorder for over 30 years, without becoming an established therapeutic approach. Interest in this class of drugs has been rekindled by the discovery that LTCC genes are part of the genetic aetiology of bipolar disorder and related phenotypes. We have therefore conducted a systematic review of LTCC antagonists in the treatment and prophylaxis of bipolar disorder. We identified 23 eligible studies, with six randomised, double-blind, controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 99 publications
(118 reference statements)
0
90
0
Order By: Relevance
“…Firstly, characterization of the complement of full-length CACNA1C isoforms is a necessary first step towards understanding how its transcript profile might be altered by a risk variant or disease state. Secondly, calcium channel blockers, which have Ca V 1.2 as one of their primary targets, are licensed for cardiovascular indications and have possible utility as a therapeutic strategy for psychiatric disorders [54][55][56][57] . Since the Ca V 1.2 proteins that arise from CACNA1C splicing show differential sensitivity to the existing calcium channel blockers 52 it may be possible to selectively target disease-relevant CACNA1C isoforms and/or those that are differentially expressed in the brain vs. the periphery, to provide novel psychotropic agents that are both more potent and are freer from peripheral side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, characterization of the complement of full-length CACNA1C isoforms is a necessary first step towards understanding how its transcript profile might be altered by a risk variant or disease state. Secondly, calcium channel blockers, which have Ca V 1.2 as one of their primary targets, are licensed for cardiovascular indications and have possible utility as a therapeutic strategy for psychiatric disorders [54][55][56][57] . Since the Ca V 1.2 proteins that arise from CACNA1C splicing show differential sensitivity to the existing calcium channel blockers 52 it may be possible to selectively target disease-relevant CACNA1C isoforms and/or those that are differentially expressed in the brain vs. the periphery, to provide novel psychotropic agents that are both more potent and are freer from peripheral side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding sleep it has been shown, that a specific CACNA1C gene is associated with sleep quality and may be associated with sleep latency, which is prolonged in CH patients . Thus, L‐type calcium channel antagonists may normalize sleep . A recent study from our own group found that CH patients taking verapamil had a later nocturnal attack peak compared to CH patients not taking verapamil (02:43 AM compared to 01:53 AM) .…”
Section: Side Effects and Safetymentioning
confidence: 96%
“…A single neuron will typically express different receptor subfamilies . CCBs are currently used in the treatment of neurological and psychiatric disorders such as epilepsy, Parkinson’s disease, dementia, bipolar disorder, and long‐term depression . Dementia and Parkinson’s diseases are neurodegenerative disorders, whereas CH, epilepsy, depression, and bipolar disorders have a cyclic nature with a possible, common hypothalamic link .…”
Section: Side Effects and Safetymentioning
confidence: 99%
“…A recent review found no evidence that verapamil, an L-type calcium channel blocker usually prescribed for cardiovascular pathology, was effective in the management of acute mania. 38 However, the review suggests that this might be due to poor blood-brain barrier permeability of verapamil. There are also concerns about cardiovascular side effects of using L-type calcium channel blockers in bipolar disorder.…”
Section: It Wasmentioning
confidence: 99%